Sustainable aviation fuel: what does it mean for airport expansion? - Eastham,S (Grantham Institute, Imperial College London, 2025)
This background briefing explores the topic of ‘sustainable aviation fuels’ (or SAFs), including their history, why they have been slow to scale-up, which cost and resource barriers will persist, and why SAFs are unlikely to be the game-changer that many are hoping for when it comes to solving the climate change questions raised by Heathrow expansion.